Platelet-derived growth factor agonist activity of a secreted form of the v-sis oncogene product. - Johnsson, A (1985)
We have compared the functional properties of a growth factor partially purified from medium conditioned by simian sarcoma virus-transformed cells with those of platelet-derived growth factor (PDGF). The factor mimicked the effects induced by PDGF: it bound to and activated human fibroblast PDGF receptors and stimulated DNA synthesis. These activities were specifically inhibited by PDGF antibodies and thus elicited by a factor(s) immunologically related to PDGF. The factor behaved as a secretory protein, since about 95% of the receptor-binding activity was found in the medium after a 48-hr serum-free incubation. Structural characterization of the PDGF-like activity revealed a Mr 24,000 intracellular protein and two polypeptides of Mr 13,000 and 11,500 released into the medium. The Mr 13,000 component bound to human fibroblasts; this binding was competitively inhibited by PDGF. The data support the possibility that oncogene products may elicit transforming activity by interacting with the normal cellular mitogenic pathway.